2010
DOI: 10.3998/ark.5550190.0010.e08
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, reactions and antitumor activity of new β-aminovinyl 3-pyrazolyl ketones

Abstract: A new series of enaminones 4a-e was prepared and their reaction with the hydrazonoyl chloride 2c gave 3,4'-bis(pyrazolyl)ketones 8a-d. Hydrazinolysis of 8 proved to be site selective as it yielded the respective 4-(pyrazol-3-yl)-2H-pyrazolo[3,4-d]pyridazines 9. The results of screening of the antitumor activity of enaminones 4a-e against human breast cell line MCF-7 revealed that all such compounds exhibited lower activity in relation to the reference drug Doxorubicin and the activity of the enaminone having e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In our hands, reaction of 6c with 3-amino-1,2,4-triazole, in ethanol in the presence of a catalytic amount of piperidine under reflux, was found to be regiospecific as it afforded only one product that was identified as 5-(4-benzoyl-1,5-diphenyl-1H-pyrazol-3-yl)-1,2,4-triazolo[1,5-a]pyrimidine 9 on the basis of its spectral data and elemental analysis. For example, its 1 H NMR spectrum revealed a one proton singlet at δ 8.46 and two doublet signals, each for one proton, at δ 7.58 and 8.84 with J = 4.5 Hz assignable to the H-2, H-6 and H-7 protons of the 1,2,4-triazolo [1,5-a]pyrimidine moiety, respectively. [13][14][15][16][17] The chemical shift value (δ 8.46) fully confirms that the condensation of 6c with 3-amino-1,2,4-triazole provides…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our hands, reaction of 6c with 3-amino-1,2,4-triazole, in ethanol in the presence of a catalytic amount of piperidine under reflux, was found to be regiospecific as it afforded only one product that was identified as 5-(4-benzoyl-1,5-diphenyl-1H-pyrazol-3-yl)-1,2,4-triazolo[1,5-a]pyrimidine 9 on the basis of its spectral data and elemental analysis. For example, its 1 H NMR spectrum revealed a one proton singlet at δ 8.46 and two doublet signals, each for one proton, at δ 7.58 and 8.84 with J = 4.5 Hz assignable to the H-2, H-6 and H-7 protons of the 1,2,4-triazolo [1,5-a]pyrimidine moiety, respectively. [13][14][15][16][17] The chemical shift value (δ 8.46) fully confirms that the condensation of 6c with 3-amino-1,2,4-triazole provides…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that heterocyclic enaminones of types 1 and 2 (Scheme 1) each exhibited an unexpected activity against the human breast cancer cell line MCF-7. [1][2][3] Also, several reports indicate that cyclic enaminones of type 3a-d (Scheme 1) proved to exhibit anticonvulsant properties and represent a new exciting series of compounds with efficacy in reducing seizures and hence are of great potential for the treatment of epilepsy. [4][5][6][7][8][9][10][11] In the light of these findings and in continuation of our recent work on the utility of enaminones for synthesis of hetaryl-pyrazoles, 1,2 it was thought interesting to synthesise new substituted enaminones 6 (Scheme 2) and explore their antitumor activity to shed some light upon structure activity relationships (SAR) and to study their reactions with some nitrogen and carbon nucleophiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these findings, formazans and heterocyclic hydrazones are known for their diverse biological activities. [10][11][12] As part of our ongoing interests in the reactions of hydrazonoyl halides with several heterocyclic compounds to synthesise bioactive compounds, [13][14][15] we investigated the reaction of hydrazonoyl halides with benzocyclohepten-5-one thiosemicarbazones and benzocyclohepten-5-one hydrazone to give new derivatives of thiazole and substituted formazan which were expected to be biologically active. We also elucidated the actual tautomeric structures of such thiazole derivatives as they can have one or more of eight possible tautomeric forms (Scheme 2 and Fig.…”
mentioning
confidence: 99%
“…Enaminones of type I have been reported to couple with arenediazonium salts to give the respective hydrazones II (Scheme 1). [1][2][3][4] In conjunction with our recent work on bisenaminones of type III, [5][6][7][8][9][10] we decided to study their azo coupling with diazotised aromatic and heterocyclic amines and to explore the reactions of the resulting azo-coupled products IV and V with hydrazine hydrate. Our aim was to shed some light on the site selectivity in the latter reactions and explore their utility to synthesise new ter-heterocycles of type VI and VII (Fig.…”
mentioning
confidence: 99%